Postcolonialism, Decoloniality and Development - McEwan, Cheryl, author.
1 online resource (488 pages)
Keywords: Postcolonialism, Decoloniality and Development is a comprehensive revision of Postcolonialism and Development (2009) that explains, reviews and critically evaluates recent debates about postcolonial and decolonial approaches and their implications for development studies. By outlining contemporary theoretical debates and examining their implications for how the developing world is thought about, written about and engaged with in policy terms, this book unpacks the difficult, complex and important aspects of the relationships between postcolonial theory, decoloniality and development studies. The book focuses on the importance of development discourses, the relationship between development knowledge and power, and agency within development. It includes significant new material exploring the significance of postcolonial approaches to understanding development in the context of rapid global change and the dissonances and interconnections between postcolonial theory and decolonial politics. It includes a new chapter on postcolonial theory, development and the Anthropocene that considers the challenges posed by the current global environmental crisis to both postcolonial theory and ideas of development. The book sets out an original and timely agenda for exploring the intersections between postcolonialism, decolonialism and development and provides an outline for a coherent and reinvigorated project of postcolonial development studies. Engaging with new and emerging debates in the fields of postcolonialism and development, and illustrating these through current issues, the book continues to set agendas for diverse scholars working in the fields of development studies, geography, anthropology, politics, cultural studies and history.